Solution of plane nonlinear stochastic problem with spectral representation method - N. N. Popov; L. V. Kovalenko; M. A. Yashin (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2009)
Solution of a stress condition of stochastic heterogeneous plate problem was obtained on the basis of statistic linearization of determinative creep equation and by using a method of spectral representation of random functions. Stochasticity is introduced into determinative creep equation by random function of two variables. It was proved, that stochastic nonhomogeneities of material can lead to significant fluctuations of stress fields.